Hezbollah: a short history - Norton, Augustus R. (Princeton studies in Muslim politics, 2007)
"Most policymakers in the United States and Israel have it wrong. Hezbollah isn't a simple terrorist organisation - nor is it likely to disappear soon." "The most accessible, informed, and balanced analysis of the group yet written, Hezbollah is essential reading for anyone who wants to understand the Middle East."--BOOK JACKET